CONTROL VOLUME ANALYSIS OF UNSTEADY MHD MIXED CONVECTION NANOFLUID FLOW ON A STRETCHING SURFACE WITH SUNCTION - Kitetu, V. M.; Onyango, T. T. M.; Kwanza, J. K. (Machakos University, 2019)
Many heat transfer processes in engineering problems in areas such as nuclear reactors and electronics, as well as in biomedicine and food industry require the knowledge of nanofluids, consequently investigations leading to understanding of the role played by nanofluids in heat transfer enhancement in these processes is vital. Currently, numerous studies are being conducted on nanofluids for the benefits associated with low energy costs and less negative environmental impact in industry and society. In the studies, water is commonly used as base for nanofluids in heat transfer applications due to its ability and availability for heat transport. In most of these investigations influence of nanoparticles have been analysed to determine enhancement of energy transfer on stretched sheets. In our research, magnetohydrodynamic mixed convection flow of a nanofluid over a stretching sheet with water equally as the base fluid and either Copper or Silver as nanoparticles is examined and analyzed. The physical problem is modeled using systems of unsteady nonlinear differential equations (DE) subject to prescribed boundary and initial conditions, which are then studied using Finite volume approach. These DE comprise of the classical continuity, momentum, concentration and energy equations, which are subsequently non dimensionalized and discretized in rectangular domain. The effect of nanoparticle volume fraction, Hartmann number, suction and stretching parameter values on and characteristics of velocity, temperature and concentration profiles, and skin friction, heat transfer, and mass transfer coefficients are discussed.
Keywords: Nanofluid; straight stretching surface; mixed convection; finite volume method